2017
DOI: 10.1186/s40001-017-0244-2
|View full text |Cite
|
Sign up to set email alerts
|

The 3-dimensional miniplate is more effective than the standard miniplate for the management of mandibular fractures: a meta-analysis

Abstract: PurposeThe study aimed to determine the superiority between 3-dimensional (3D) miniplate and standard miniplate for mandibular fractures (MFs) treatment.BackgroundControversial results on the use of standard miniplate and 3D miniplate have remained for management of MFs.MethodsSeveral electronic databases were retrieved up to September 2014 to identify eligible studies. The quality of studies was assessed, and the relative risk (RR) with its corresponding 95% confidence interval (CI) was assessed to measure th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…This was insignificant due the established fact that nerve affection in MAFs depended mainly on the preoperative degree of displacement of the segments (9) . This was confirmed in other studies which did not identify any difference after surgery regarding the presented paresthesia (17) .…”
Section: Discussionsupporting
confidence: 85%
“…This was insignificant due the established fact that nerve affection in MAFs depended mainly on the preoperative degree of displacement of the segments (9) . This was confirmed in other studies which did not identify any difference after surgery regarding the presented paresthesia (17) .…”
Section: Discussionsupporting
confidence: 85%
“…In regard to post-operative infection, wound dehiscence and paresthesia, both methods provided similar results [ 18 ]. Conversely, post-operative complications, such as mal-occlusion and trismus, appear to occur more frequently when fractures are fixed using conventional miniplates [ 9 , 20 ]. These findings are in agreement with Mohd et al (2019) [ 21 ], who showed a lower mobility and improved occlusion restoration for parasymphisis fractures treated with 3D miniplates.…”
Section: Discussionmentioning
confidence: 99%
“…All screws were designed as cylinders with 2 mm diameter and 6 mm in length. All mini-plates with 2 mm thickness had four screw holes [ 6 , 20 , 31 ]. And the biomechanical properties of the fractured mandible fixed with the two different fixation systems were calculated by finite element analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, there are two typical treatment modalities for the mandibular angle fractures: the first one uses one mini-plate for fixation, which has been widely used during the past two decades, following the principles described in 1975 by Champy [ 6 8 ]; the other one uses two mini-plates [ 9 ], with a upper mini-plate fixed at the same place of previous treatment which corresponds to the tension band of the mandible, and the lower mini-plate fixed at the inferior border of the mandible which corresponds to the compression band of the mandible. However, all the mini-plates used in the clinical case are standard and straight plates, and need to be bent to bone surface before fixation, which will increase the time of the operation and may lead to mismatching between the bone surface and titanium plates [ 10 ].…”
Section: Introductionmentioning
confidence: 99%